ANALISIS FAKTOR RISIKO HIPERTENSI: STUDI KASUS KETERKAITAN PARITAS, UMUR, DAN INDEKS MASSA TUBUH - Yulita, Hendra; Suyati, Suyati; L.Tobing, Hendri Parluhutan; Sada, Merinta; Syarif, Afwan (Ensiklopedia of Journal, 2024)
Abstract: Pangkalan Kerinci I Health Center is one of the health centers in Pelalawan Regency with the highest cases of hypertension in pregnant women. Some factors that can cause hypertension in pregnant women are parity, maternal age and body mass index. The purpose of the study was to determine the relationship between parity, maternal age and body mass index on the incidence of hypertension in pregnant women. This type of research is quantitative with a cross sectional design. This research was conducted in the work area of UPT Puskesmas Pangkalan Kerinci in November-December 2023. The study population was all pregnant women registered at UPT Puskesmas Pangkalan Kerinci, totaling 175 people, while the study sample amounted to 64 people. The sampling technique used accidental sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed there was a relationship between parity (p value: 0.029), maternal age (p value: 0.003) and body mass index (p value: 0.017) to the incidence of hypertension in pregnant women. It is recommended to the health center to conduct health promotion to pregnant women during posyandu activities about the importance of conducting pregnancy checks, because in carrying out Antenatal Care services, there are ten service standards that must be carried out by midwives or health workers known as 10 T and one of them is checking blood pressure.Keywords: Pregnant Women, Parity, Age.